Prevalence, risk factors and transmission of streptococcus agalactiae in the red hybrid tilapia (Oreochromis Sp.) - Azmai, Mohammad Noor Amal (2011)
Outbreak of Streptococcus agalactiae infection in fish was first reported in Malaysia in late 1990s in Pahang river, Pahang, affecting floating net cage-cultured red tilapia (Oreochromis sp.). Since then, outbreaks of S. agalactiae infection in tilapia have been widespread, covering almost all parts of Peninsular Malaysia. Presently, S. agalactiae infection has become a leading disease that has severe economic impact to the tilapia farming industry not only in this country but all over the world. Therefore, concrete understanding on the epidemiology of this disease is essential in order to control and prevent the infection. This study was conducted to understand the prevalence, clinical signs and pathological changes, risk factors from water quality and transmissions of S. agalactiae in the red hybrid tilapia (Oreochromis sp.) floating net cage culture system.The prevalence of S. agalactiae in red hybrid tilapia cultured in different types of water bodies was investigated for a period of 24 months. The study was conducted at five types of water bodies consisting of two huge-sized reservoirs (Kenyir Lake, Terengganu and Pedu Lake, Kedah), a moderate-sized Terengganu river with four sampling sites along the river (Beladau Selat, Beladau Kepong, Pantai Ali and Kuala Kejir, Terengganu), a small-sized pond (Jitra, Kedah), a small-sized irrigation canal (Kodiang, Kedah) and a small-sized ex-mining pool (Pantai Kamloon, Penang). This study involved monthly sampling of 30 red hybrid tilapias for bacterial isolations, measurement of water quality such as water temperature, dissolved oxygen and pH by using hand-held YSI meter (YSI Incorporated, USA) and ammonia, iron, nitrite and sulfide by using spectrophotometers (HACH Company, USA). For water flow, water clarity and depth at culture sites, the readings were measured using a current water meter (Global Water, California), Secchi disc and ultrasonic depth sensor (Speedtech Instrument, USA), respectively. All of the measurements were taken at 1 m deep involving four consistent sampling points within and surrounding the cages. With regard to the type of water bodies, the mean prevalence of red hybrid tilapia that were cultured positive to S. agalactiae was significantly higher (p<0.05) in huge-sized with very slow water flow (0.006±0.003 cm/s) reservoirs (12.49±19.84%), compared to moderate-sized with moderate water flow (0.25±0.24 cm/s) Terengganu river (2.60±6.25%), small-sized with very slow water flow (2.78-17±0.0 cm/s) pond (0.69±2.77%), small-sized with fast water flow (0.26±0.08 cm/s) irrigation canal (0.28±0.94%) and small-sized with very slow water flow (2.78-17±0.00 cm/s) ex-mining pool (0.17±0.82%). There was a significant positive correlation between the isolation of S. agalactiae and red hybrid tilapia mortalities (r=0.7140, p<0.05) and water temperature (r=0.5444, p<0.05) in Pedu Lake. Infections by S. agalactiae showed significant positive correlation to affect red hybrid tilapias of the size between 10 and 30 cm in length (r=0.6023, p<0.05). The overall mean rate of water flow from all sampling sites showed non significant negative correlation with the prevalence of red hybrid tilapia that cultured positive to S. agalactiae (r=-0.2645, p>0.05). There was also a significant positive correlation (r=0.9312, p<0.05) between isolations of S. agalactiae and mortalities of red hybrid tilapias in Pedu Lake, in the presence of Staphylococcus spp. The results indicate that the water temperature, rate of water flow, size of fish and the presence of other bacterial influence the prevalence of S. agalactiae in cultured red hybrid tilapia. The organs of red hybrid tilapias naturally infected by S. agalactiae were examined for pathological changes, including histopathology. Affected red hybrid tilapias showed consistent gross findings of congestion of internal organs, particularly the livers, spleens and kidneys. Other features included exophthalmos, softening of the brains and occasional accumulation of fluid within the abdominal cavity. Microscopic examination revealed swollen endothelial cells that lined the major blood vessels of livers and occasionally spleens leading to extensive infarction, while bacterial colonies were observed within and immediately surrounding the affected blood vessels. The meninges were thickened by the infiltration of numerous heterophils. Similar infiltrations of heterophils and lymphocytes were observed in the lamina propria of intestine. The kidneys were severely congested and haemorrhagic, with extensive interstitial nephritis. The lesion pattern suggested an acute systemic infection. The effect of water quality on the presence of S. agalactiae in cultured red hybrid tilapias was only done in reservoirs and river, due to the significant isolation of the pathogen in these water bodies. There were significant differences (p<0.05) in water quality between lakes and river in terms of depth at culture sites, iron, ammonia, pH, sulfide, temperature, water clarity and dissolved oxygen. There were no significant differences (p>0.05) in iron, ammonia and nitrite levels along the river but significant differences (p<0.05) were recorded for the pH, water clarity, sulfide and dissolved oxygen concentration. Furthermore, the river water temperature at two upstream sites was not significantly (p>0.05) lower than downstream. This study revealed significant positive correlation (r>0.5000; p<0.05) between certain water quality parameters and the presence of S. agalactiae, particularly the pH, temperature, clarity and dissolved oxygen in both lakes. While in river, water quality parameters such as iron, ammonia, nitrite, pH, temperature, clarity and dissolved oxygen were observed to have a significant positive correlation with the presence of S. agalactiae. The results suggest that different type of water bodies and location of culture sites can affect water quality, creating stressed environment and increased the presence of S. agalactiae in cultured red hybrid tilapia. The phenomenon on the significance of high water temperature in reservoirs and their effect to the cultured red hybrid tilapia to S. agalactiae infection was also investigated. Readings for water temperature and dissolved oxygen at 1 m intervals were collected in situ by using a hand-held YSI meter (YSI Incorporated, USA) for up to 20 m deep, at four consistent sampling points within and surrounding the cages. In Kenyir Lake, the high water temperature column (≥29oC) was mostly noted at between 0 and 8 m depth, particularly between April and November 2007 and 2008. However, in Pedu Lake, the high water temperature (≥29oC) for up to 8 m deep was recorded between April to September 2007 and 2008. Dissolved oxygen profiling in both lakes, however, remained high at >5 mg L-1 for up to 8 m deep, except for October 2007 in Kenyir Lake and April 2008 in Pedu Lake. Analysis of water quality parameters in Kenyir Lake revealed a significant positive correlation between water clarity (r=0.8823, p<0.05) and the prevalence of S. agalactiae. Significantly, water temperature also showed a negative correlation with water flow (r=-0.8584, p<0.05) and a positive correlation with water clarity (r=0.7510, p<0.05). Therefore, combinations of high water clarity, slow water flow and hot months increased the water temperature for up to 8 m deep in both reservoirs. Since red hybrid tilapias were cultured for up to ±4 m deep, this phenomenon created stressful condition and increased their susceptibility to S. agalactiae. Transmission of S. agalactiae in red hybrid tilapias from a hatchery to a newly established farm was studied in a batch of newly hatched fry. Between 30 and 200 samples of newly hatched fry, fingerlings and adults of red hybrid tilapia, together with ten samples of water at 1 m deep and sediment were collected from a fish hatchery and farm at 15- and 30-day intervals for bacterial isolation, according to a published method in literature. Results revealed that 20% of water samples, collected on day 30 and 6.7% fingerlings from hatchery, collected on day 75 were positive to S. agalactiae. Following transfer of the fry to the farm, 3.3% fish that were sampled on days 180 and 210 were positive to S. agalactiae, while on day 270, 20% of water samples from the farm were positive to S. agalactiae. Random Amplified Polymorphic DNA (RAPD-PCR) and Repetitive Polymerase Chain Reaction (REP-PCR) genotyping of the S. agalactiae isolates revealed no genetic diversity. This proved that the bacterial transmission was likely to occur during the fish and water transfer from the hatchery into the farm, while the bacterial probably originated from the environment of the hatchery and nearby irrigation canal. In conclusion, the study demonstrated that combinations of water body, poor water quality, sizes of fish and the presence of other bacterial species affect the prevalence of S. agalactiae in the cultured red hybrid tilapia. The red hybrid tilapia that naturally infected by S. agalactiae also showed an acute systemic infection and the bacterial transmissions occurred during the introduction of fish and water from hatchery into the farm.